Peran Akun Tiktok dalam Membangun Citra dan Eksistensi Pemuda Panca Marga di Kalangan Generasi Muda - Mochamad Taufik Saeful Anwar; Mecky Pirsouw; Maudhy Satyadharma; Tina Trisarana Andriani Silondae (Jurnal Ilmu Sosial dan Humaniora, 2025)
In today's digital era, social media plays a crucial role in shaping public opinion and organizational presence. TikTok, as one of the most popular social media platforms among young people, holds significant potential for disseminating information and building organizational image. This article discusses how Pemuda Panca Marga (PPM) can utilize its TikTok account to build a positive image and strengthen the organization's presence in the community, particularly among the younger generation. This research uses a descriptive qualitative approach using literature review and content observation methods. The analysis shows that TikTok, as a short video-based social media platform, has significant potential for building a positive image and strengthening Pemuda Panca Marga's presence in the community, particularly among the younger generation. Through creative, educational, and inspirational content, the PPM Chairman's personal TikTok account can reintroduce fighting values, revitalize nationalism, and effectively expand the reach of organizational information.